2007
DOI: 10.1159/000099095
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Calcification Inhibition Proteins and Coronary Artery Calcium Score: Comparison between Transplantation and Dialysis

Abstract: Vascular calcifications in CKD are now linked to serum alterations of both divalent ions and calcification inhibitory proteins. Due to possible biochemical differences between dialysis (D) and transplantation (Tx), we examined the entity and severity of these biochemical modifications and of coronary artery calcium score separately in these two populations. We assayed, besides standard markers of inflammation, divalent ions and serum levels of fetuin, matrix Gla protein (MGP) and osteoprotegerin (OPG), in 51 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 87 publications
5
40
0
3
Order By: Relevance
“…As in most other studies examining dialysis (Kraśniak et al 2007) or Tx patients (Rosas et al 2005;Mazzaferro et al 2007;Seyahi et al 2011) CAC significantly correlated with age in both examined groups. In addition, patients from both subgroups with CAC had undergone significantly longer CKD and/or dialysis duration than patients without CAC.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As in most other studies examining dialysis (Kraśniak et al 2007) or Tx patients (Rosas et al 2005;Mazzaferro et al 2007;Seyahi et al 2011) CAC significantly correlated with age in both examined groups. In addition, patients from both subgroups with CAC had undergone significantly longer CKD and/or dialysis duration than patients without CAC.…”
Section: Discussionsupporting
confidence: 82%
“…By searching Medline and PubMed databases, Hamirani et al (2008) found variable association between CAC and inflammation in the general population. Nevertheless, in Tx patients (Mazzaferro et al 2007) and dialysis patients (Kraśniak et al 2007;Coen et al 2006), this relationship was closer in cross-sectional studies and in CAC progression investigations (Mazzaferro et al 2009;Coen et al 2010).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Restricting the analysis to patients with a baseline score > 0 (n = 161) did not change the results (data not shown). Older age and male gender are classical CV risk factors (23,24,18,40). Like for CAC progression, use of statin and baseline score were associated with AoC progression.…”
Section: Discussionmentioning
confidence: 99%